Genetic Approach on Sanionia uncinata (Hedw.) Loeske to Evaluate Representativeness of in situ Conservation Areas Among Protected and Neighboring Free Access Areas in Maritime Antarctica and Southern Patagonia - Hebel, Ingrid; Gonzalez, Inti; Jaña, Ricardo (Frontiers in Conservation Science, 2021)
The Antarctic Specially Protected Areas (ASPAs) are zones with restricted access to protect outstanding environmental, scientific, historic, aesthetic, or wilderness values adopted inside the Antarctic Treaty System. Meanwhile, in southern Patagonia, conservation initiatives are implemented by the state of Chile and private entities. However, both are considered unrepresentative. Our work evaluates the representativeness of the in situ conservation through an genetic approach of the moss Sanionia uncinata (Hedw.) Loeske among protected and neighbouring free access areas in Maritime Antarctica and southern Patagonia. We discuss observed presence with both current and reconstructed past potential niche distribution (11 and 6 ka BP) in the Fildes Peninsula on King George Island. Results showed occurrence of several spatially genetic subpopulations distributed inside and among ASPA and free access sites. Some free access sites showed a higher amount of polymorphism compared with ASPA, having ancestry in populations developed in those places since 6 ka BP. The different spatial and temporal hierarchies in the analysis suggest that places for conservation of this species in Maritime Antarctica are not well represented and that some free access areas should be considered. This work represents a powerful multidisciplinary approach and a great challenge for decision-makers to improve the management plans and the sustainable development in Antarctica.